Desempenho de fosfitos de potássio no manejo de mofo branco em soja - Camochena, Rubia Cristiani (2015)
Soybean plays an important role in the Brazilian agriculture being one of the products most exported by the country. Its yield may be affected by diseases such as white mold, caused by the fungus Sclerotinia sclerotiorum Lib. de Bary, which, under favorable field conditions prevents the crop of expressing all its productive potential. The fungus is cosmopolitan and infects more than 400 species of plants. This disease is difficult to control, and the use of chemicals has not been sufficient to avoid significant losses, thus, this products are expensive and may cause environmental damage. Alternative methods, such as foliar fertilizers based on potassium phosphite, can also be used in the management of this disease. In this context, this work aimed to study different sources of potassium phosphite and its effects in the control of white mold in soybeans, as well as the time of application in culture, its action in inducing plants defense responses and/or its influence over the seeds quality. The effect of phosphites, over the pathogen, was evaluated in vitro, on mycelial inhibition, the mass of dry mycelium and germination of sclerotia. In all tests, the following phosphites were utilized: Phosphite A (P2O5-40%; K2O-20% - 1 L/ha); Phosphite B (P2O5-40%; K2O-28% - 1 L/ha); Phosphite C (P2O5-40%; K2O-20% - 1 L/ha) e Phosphite D (P2O5-30%; K2O-20% - 2,4 L/ha). At the induction of resistance tests were evaluated the synthesis of phytoalexin in soybean cotyledons and the enzymes FAL and POX evaluated in seedlings in growing chamber, sprayed with phosphites and the fungicide fluazinam. Field experiment was carried out at Coronel Domingos Soares-PR, in the 2012/2013 season, in an area with natural infestation of the pathogen. Soybean cultivar BMX Active was no-till seeded with 0,5m between rows. The experimental was laid out as a factorial 5 x 4 scheme (treatment x application time). Phosphites sources were used, as described above, and water was sprayed in the control treatment. Treatments were applied at four different growth stages: V4, V4 + R1, R1 and R2 at the rates recommended by the manufacturer. Soybean yield components and seeds and health and physiological quality were evaluated after harvesting. None of the tested phosphites affected mycelial growth and sclerotia germination or influenced phytoalexin synthesis. Phosphites C and D stood out due to an increasing in the phenylalanine ammonia-lyase activity 48 hours after its inoculation. These same products also induced the synthesis and peroxidases and phosphite C kept the levels of this enzyme elevated up to 72 hours after inoculation. At the field trials, phosphites C and D stood out in the control of white mold. There was no significant interaction of potassium phosphite on physiological and sanitary quality of the seeds.